2019
DOI: 10.30802/aalas-cm-18-000036
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Growth Kinetics and Spontaneous Metastasis in the B16F10 Syngeneic Murine Melanoma Model

Abstract: Melanoma is an immunogenic tumor that can metastasize quickly to proximal and distal sites, thus complicating the application of therapeutic modalities. Numerous mouse model systems have been used to gain understanding of the immunobiology and metastatic potential of melanoma. Here, we report the optimization of a syngeneic mouse melanoma model protocol using the mouse B16-derived melanoma cell line B16F10 that ensures the production of tumors on mice pinnae that are similar in size between animals and that en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Lung tissue harbors many immune cells, and is a site of metastasis for B16F10 murine 61 and human melanoma. 62 , 63 IC expression changes with age could influence metastatic tumor spread or ICI response there.…”
Section: Resultsmentioning
confidence: 99%
“…Lung tissue harbors many immune cells, and is a site of metastasis for B16F10 murine 61 and human melanoma. 62 , 63 IC expression changes with age could influence metastatic tumor spread or ICI response there.…”
Section: Resultsmentioning
confidence: 99%
“…VC2 virus was grown and titrated in Vero cells (ATCC), as described previously (65). and B16F10n-1 cells were engrafted orthotopically in the dermis of the dorsal left dorsal pinna, as previously reported (66). Mice were engrafted with 5×10 5 B16F10n-1 cells in 100 μL PBS.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Furthermore, several studies have also suggested that NTP therapy of primary tumors may have an effect at distant, untreated tumor sites. 15 , 53 , 54 While we did not observe any metastatic lesions in any of our tumor‐bearing mice (treated or untreated), more sophisticated models 55 will need to be used to fully evaluate NTP effect on secondary and metastatic tumors. These promising responses to NTP treatment require more detailed studies into not only the underlying mechanisms, but also into how NTP can be controllably dosed to bring about a predictable therapeutic response.…”
Section: Discussionmentioning
confidence: 85%